Economic convergence and divergence in Europe : growth and regional development in an enlarged European Union - Tumpel-Gugerell, Gertrude; Mooslechner, Peter; Oesterreichische Nationalbank (Cheltenham, UK ; Northampton, MA, USA : Edward Elgar, 2003)
This highly topical book addresses the challenges of economic convergence within Europe, beginning with a thorough review of the theory of growth and related empirical research.
Includes bibliographical references and index.
osc 01/09/16
Loans
Keywords: Economic Integration; Economic policy; European Union; European Union countries; Europe, Central